Faktor-Faktor yang Memengaruhi Ketimpangan Distribusi Pendapatan Provinsi Jawa Tengah - Darwin Hartono (Neolectura, 2020)
The purpose of this research is to find out the effect of population growth, inflation and the provincial minimum wage toward inequality of income distribution in Central Java Province in 1997-2012. The method used in this research is quantitative descriptive analysis method using secondary data that is the time series in 1997-2012. The analytical tool used in this study is multiple linear regression, as the dependent variable used is the gini index and the independent variables are population growth, inflation and the provincial minimum wage by testing classical assumption and statistical testing.